"Nie ma terminu, który by nie nadszedł, ani długu, którego nie trzeba by spłacić". Jeszcze o "Don Juanie" w "Dziadach" = "There Is No Time Limit That Does Not Arrive nor Any Debt That Is Not Paid". More on "Don Juan" in the "Forefathers' Eve" - Narolska, Aneta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The aim of the study is an interpretation of Scene VIII of Mickiewicz's Dresden "Forefathers' Eve" (Part Three) ["Dziady"] in the context of two Don Juan dramas: Tirso de Molina's "The Trickster of Seville and the Stone Guest" ["Zwodziciel z Sewilli i Kamienny Gość"] and Moli?re's "Don Juan, or the Stone Guest" ["Don Juan, czyli Kamienny Gość"]. Mozart's opera "Don Giovanni, or the Rake Punished" ["Don Giovanni albo Rozpustnik ukarany"], being a synthesis of earlier versions of the Don Juan story, is treated here as the surface layer under which there are a number of relationships between Mickiewicz's text and works drawing on the Spanish legend. The composition of Scene VIII, the construction of the character (Senator), and humour are the elements that link Mickiewicz's text with Moli?re's drama. What link "Forefathers' Eve" with Spanish drama are its morality-play nature and the message about damnation for unbelief in the existence of Divine reality and justice. Therefore, the scene of the Ball at the Senator's not only attests to a link between Mickiewicz's drama and the Moli?rean tradition but may also point to an indirect link with Golden Age Spanish drama.
Keywords: Don Juan; dramat; "Dziady" drezdeńskie; drama; Dresden "Forefathers' Eve"